2006
DOI: 10.1002/pmic.200500896
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression changes in human cells after exposure to mobile phone microwaves

Abstract: Possible biological effects of mobile phone microwaves were investigated in vitro. In this study, which was part of the 5FP EU project REFLEX (Risk Evaluation of Potential Environmental Hazards From Low-Energy Electromagnetic Field Exposure Using Sensitive in vitro Methods), six human cell types, immortalized cell lines and primary cells, were exposed to 900 and 1800 MHz. RNA was isolated from exposed and sham-exposed cells and labeled for transcriptome analysis on whole-genome cDNA arrays. The results were ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 28 publications
(11 reference statements)
4
54
0
1
Order By: Relevance
“…These findings are supported by several gene-array studies showing significant shifts in the expression of a small subset of genes following RF irradiation [e.g. Remondini et al, 2006;Belyaev et al, 2006], Dawe et al 4 although other gene-array studies have reported no significant changes [Qutob et al, 2006;Whitehead et al, 2006;Gurisik et al, 2006]. The RF fields used in these vertebrate cell culture studies were pulsed (GSM) and more intense (SAR ~2.0 W kg -1 ) than those used in the nematode work (SAR 5-40 mW kg -1 CW), raising the possibility that apparent differences between studies on nematodes and on vertebrate cells may reflect modulation and/or dose.…”
Section: Introductionsupporting
confidence: 64%
“…These findings are supported by several gene-array studies showing significant shifts in the expression of a small subset of genes following RF irradiation [e.g. Remondini et al, 2006;Belyaev et al, 2006], Dawe et al 4 although other gene-array studies have reported no significant changes [Qutob et al, 2006;Whitehead et al, 2006;Gurisik et al, 2006]. The RF fields used in these vertebrate cell culture studies were pulsed (GSM) and more intense (SAR ~2.0 W kg -1 ) than those used in the nematode work (SAR 5-40 mW kg -1 CW), raising the possibility that apparent differences between studies on nematodes and on vertebrate cells may reflect modulation and/or dose.…”
Section: Introductionsupporting
confidence: 64%
“…The complex field patterns, with variable peak field strengths and intervals between transmissions, may influence biology in ways that controlled, simulated patterns cannot, but they are not represented by time-averaged, duty factor reductions of described energy absorption. Responses to RF fields can be greater for intermittent exposures than continuous (15,16) and depend upon the pulse characteristics for the same average power (17). Effects can be dependent on frequency, modulation, signal strength (intensity windows), durations of exposure and polarisation (18,19).…”
Section: Scientific Accuracymentioning
confidence: 99%
“…17,18 When the cells are irradiated with low power settings (240 W with up to 15 cycles and 420 W with 6 cycles of 5 s), an increase in ATP production above control levels is observed, indicating an enhancement in cellular metabolism or growth. Higher powers of irradiation, however, cause increasing levels of cellular damage indicated by the decrease in ATP production.…”
Section: Microwave For Gene/oligonucleotide Deliverymentioning
confidence: 99%
“…The primer sequences for the RT-PCR reaction were Ex20Fo 5 0 -CAGAATTCTGCCAATTGCTGAG-3 0 and Ex26Ro 5 0 -TTCTTCAGCTTGTGTCATCC-3 0 for amplification of mRNA from exon 20 to 26. 17 The cycling conditions were 95 1C for 1 min, 55 1C for 1 min, 72 1C for 2 min for 30 cycles. The reaction mix consists of 1 Â PCR buffer (Invitrogen), 10 mM of each dNTP, 0.6 mM of each primer and 2.5 mM MgCl 2 .…”
Section: Aon Rna Extraction and Rt-pcrmentioning
confidence: 99%